Selectivity Estimates for Sardinella longiceps (Valenciennes) in the Gill Net Fishery off Cochin - Thomas, Saly N.; C., Hridayanathan (Fishery Technology, 2025)
Length frequency of sardine, Sardinella longiceps (Valenciennes), caught in gill nets with mesh size of 32, 34, 36, 38 and 40 mm operated off Cochin (Kerala) was recorded. Using this, the selectivity parameters of the nets of these mesh sizes were assessed. The size range of S. longiceps caught was 12 to 20 cm. The estimated selection factors ranged from 4.56 to 4.67 and the selection lengths ranged from 14.7 to 18.7 cm. Gill nets with mesh size less than 34 mm did not facilitate the escapement of S. longiceps which had not attained the stage of first maturity.